Analisis Minat Berperilaku Mahasiswa Dalam Menggunakan Teknologi Informasi - Sumarsono Sumarsono (Jurnal Ekonomi Bisnis dan Akuntansi (JEBA), 2011)
ABSTRACT This study investigates application of  behavior information technology acceptance using Davis’ Technology Acceptance Model. This model is used to explain the impact of social influence, perceived usefulness, perceived ease of use, and psychological attachment and intention to use in information technology.. The respondents were 119 Jenderal Soedirman University students. Data was collected by questionnaire and then analyzed by using Structural Equation Modeling (SEM). The results shows that social influence, perceived usefulness,  and psychological attachment have a positive and significant influence to student intention to use in information technology. But  perceived ease of use have no impact on student intention to use information technology.  The result of this study is expected to be inputs for faculty and university and especially for the policy makers so that can stimulate and encourage Jenderal Soedirman University students to use information technology in their learning activities. Keywords:   social influence, perceived usefulness, perceived ease of use, psychological attachment, intention to use information technology